Estudo da influência do tempo de cura no comportamento mecânico das misturas entre solos e altos teores de emulsão asfáltica - Oliveira Brito, Nátalia Jéssica Canuto (2020)
The use of asphalt mixtures as a soil stabilizing agent is an alternative that can be used in numerous geotechnical works. The objective of this research was to study the effects of curing and aeration time of mixtures between soil and high levels of asphalt emulsion on their mechanical behavior. The methodology adopted consisted of collecting and characterizing sandy soil and asphalt emulsion, mixing and compacting materials with different levels of emulsion, exposing the test pieces to the open air (for curing to occur), performing simple compression tests of the compacted soil and soil-emulsion mixtures for different curing times, as well as a triaxial compression test, for optimum levels of asphalt emulsion. This was done with and without saturation of the specimens, with and without aeration time, and for different curing times of the mixtures (1, 7 and 28 days). The results showed that, for the tested soil-emulsion mixtures, the increase in the curing time caused a gradual decrease in the apparent specific mass of the specimens, due to the decrease in the moisture content due to the breakage of the emulsion. In the simple compression tests, it was noted that the soil-emulsion mixtures presented much higher resistances compacted soil. Furthermore, the longer the curing time of the mixtures, the greater the resistance to compression. For the triaxial compression tests, it was possible to observe that the addition of the highest levels of asphalt emulsion to the sandy soil increased the value of the cohesive intercept, at the same time that it significantly decreased its friction angle. Under saturated conditions, the curing time did not significantly affect the shear strength and the stiffness of the mixtures. However, in triaxial tests performed on samples in unsaturated conditions, the curing time influenced these parameters considerably, being in this case directly proportional to the stiffness and the value of the cohesive intercept. The results referring to compacted mixtures after 24 hours from the moment of mixing the soil with the emulsion (M24) and shortly after the combination of these materials (MI) showed that the MI mixture had higher values ​​of shear strength and stiffness than M24. However, both had a similar cohesive intercept, although M24 had a lower friction angle. In general, it was observed the stabilization of the studied sandy soil, due to the change in the shearing behavior of the mixtures. It was also concluded that the curing and the aeration time led to changes in the shear strength properties in unsaturated conditions, with an increase in the curing time. Thus, such mixtures must be considered as viable alternatives in geotechnical works where there are scarcity of materials, and mainly, in works that demand cohesive and low permeability materials.